Bitter Coffee for Sweet Diabetes: A Randomized Controlled Trial For Treatment Of Type 2 Diabetes With Black Coffee In Balb c Albino Mice - Butt, Jawaria; Naeem, Uzma; Lodhi, Sadia; Khokhar, Aamna; Azeem, Abdul; Tayyab, Mehwish (Pakistan Journal of Physiology, 2021)
Background: Diabetes Mellitus is a chronic metabolic ailment which slowly but surely harms the human body if left untreated. The objective of this study was to determine the effect of black coffee on HbA1C, fasting and postprandial blood sugar levels in mice model of type 2 diabetes mellitus. Methods: This was an experimental, randomized control study performed at the Pharmacology Laboratory, Multidisciplinary Research Laboratory at Islamic International Medical College and National Institute of Health (NIH) Islamabad Pakistan. The study comprised a total of 30 male Balb/c albino mice and diabetes was induced in experimental group (n=20) by using low dose streptozotocin (40 mg/Kg). After confirmation, diabetic mice were further divided into two groups of 10 each. Group 2 was diabetic control and Group 3 was treated with black coffee for 45 days. Blood samples were taken from lateral tail vein for fasting and post prandial blood sugar levels and by intracardiac puncture for HbA1c. Statistical analysis was done on SPSS-21. Comparisons between the groups were analyzed using one way ANOVA (post hoc tuckey test), and p<0.05 was considered significant. Results: Black coffee treated mice (Group 3) had significantly decreased serum HbA1C levels (6.02±0.29) fasting (116.8±4.92) and postprandial (173.6±18.3) blood glucose levels in comparison with those found in diabetic control mice (Group 2). Conclusion: Black coffee significantly decreases serum HbA1C, fasting and postprandial blood glucose levels in diabetic mice. Pak J Physiol 2021;17(1):15–8